Mapping the wildland-urban interface from houses locations and terrain slope in Patagonia Argentina - Sanucci, Corina (2022)
Urbanization of forested areas increases the surface of wildland-urban interface (WUI), where fire is the primary hazard for humans and ecosystems. We determined the WUI using a novel approach in NW Patagonia, Argentina and evaluated its relationship with the fire ignition points. The WUI expands a greater distance on upslopes, where the rate of fire spread is highest. The WUI reaches the maximum distance under the most hazardous conditions: houses surrounded by fuels with steep slopes towards them. In the Bariloche district in 2021, the WUI included 81% of the houses and occupied 37% (11,006 ha) of the total study area. Between 2015 and 2021, 77% of fire ignitions occurred in the WUI, highlighting the relevance of urban growth planification and the management of fuel load to reduce wildfire risk